CODE MIXING ANALYSIS IN DIVORTIARE NOVEL - Siahaan, Hiace Vega Fernando; Silitonga, Andi Jaihutan; Purba, Citra Karina (Universitas Putera Batam, 2022)
This research aimed to analyze the usage of code mixing in Divortiare novel that was written by Ika Natasssa. The objective of this research is to find out the type of code mixing that is used in Divortiare Novel. This study is a qualitative research. The technique of collecting data was done by using documentary technique. The odd number chapters in Divortiare novel are used as the data of this study. The data were analyzed by using Miles and Hubberman model. The findings of this study show that there are three types of code mixing used namely: insertion, congruent lexicalization and alternation. The result of this study showed that insertion was used 71,75%; congruent lexicalization was used 21,08% and alternation was used 7,17%. Based on the result of this study, it shows that the most dominant type of code mixing used in Divortiare novel is insertion. So, it can be concluded that the writer of the novel use insertion most dominantly cause discuss about particular topic, being emphatic about something and expressing group identity.